2014
DOI: 10.12968/denu.2014.41.9.775
|View full text |Cite
|
Sign up to set email alerts
|

Management of patients with non-syndromic clefts of the lip and/or palate part 2: from primary surgery to alveolar bone grafting

Abstract: Part 1 of this series of articles addressed the care of the child with a cleft of the lip and/or palate from antenatal diagnosis until primary surgery. The second part of this article discusses their care from primary surgery until alveolar bone grafting. Clinical Relevance: Dentists should be aware of the different types of cleft lip and/or palate that occur and the role of the dentist in the overall management of patients who have clefts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…As the patient grows older and attends further cleft MDT clinics, which include treatment planning and long-term management with orthodontic and restorative input, general dental practitioners are paramount in the shared care of these patients. 23,24 Early identification of dental anomalies is essential. Although this study explored the most commonplace dental anomalies found in cleft patients, it is worth noting that the literature also mentions other dental anomalies which may present themselves in this population.…”
Section: Implications For Dentists Working In Primary Carementioning
confidence: 99%
See 1 more Smart Citation
“…As the patient grows older and attends further cleft MDT clinics, which include treatment planning and long-term management with orthodontic and restorative input, general dental practitioners are paramount in the shared care of these patients. 23,24 Early identification of dental anomalies is essential. Although this study explored the most commonplace dental anomalies found in cleft patients, it is worth noting that the literature also mentions other dental anomalies which may present themselves in this population.…”
Section: Implications For Dentists Working In Primary Carementioning
confidence: 99%
“…It is known that cleft-affected individuals have a higher caries prevalence compared their noncleft counterparts. 23,24,26,27 As treatment plans are formulated through cleft MDTs, certain teeth may require treatment within primary dental care. For instance, shape/size anomalies may require restoration or build-up to camouflage, while certain teeth within the cleft site may require extraction if they are deemed to be of poor long-term prognosis.…”
Section: Implications For Dentists Working In Primary Carementioning
confidence: 99%
“…Patients with craniofacial cleft may require series of treatment from the time of birth to adulthood [5], and the timing for initial surgery varies among centers all over the world. This is influenced by the type of orofacial cleft, presence of other congenital anomalies, availability of medical facilities, surgeons' skills, and preferences among other factors.…”
Section: Tessier Clefts and Locationmentioning
confidence: 99%
“…1 Being born with a cleft of the lip and/or palate (CL/P) can impact several aspects of a child's life, including feeding problems, altered facial aesthetics and growth, communication difficulties and an increased risk of dental disease and malocclusion. [2][3][4][5][6] Due to an increased risk of bullying and social stigmatization as a result of their facial difference, challenges with communication and lower levels of self-esteem and self-acceptance, 7,8 it has been hypothesized that children with CL/P may present with lower levels of well-being. Despite this, a recent systematic review and metaanalysis indicated that overall children born with CL/P have similar levels of well-being when compared with their typically developing peers; however, they may experience slightly increased levels of psychological symptoms, including depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Oral clefts are the most common craniofacial abnormality worldwide, with an estimated prevalence of approximately 1.5 in every 1000 live births 1 . Being born with a cleft of the lip and/or palate (CL/P) can impact several aspects of a child's life, including feeding problems, altered facial aesthetics and growth, communication difficulties and an increased risk of dental disease and malocclusion 2–6 . Due to an increased risk of bullying and social stigmatization as a result of their facial difference, challenges with communication and lower levels of self‐esteem and self‐acceptance, 7,8 it has been hypothesized that children with CL/P may present with lower levels of well‐being.…”
Section: Introductionmentioning
confidence: 99%